The Influence of Internal Control, Financial Literacy, and Organizational Culture on Financial Performance at LPD in Kintamani District - Kadek Sutawan; Mertyani Sari Dewi; Komang Trisna Sari Dewi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the impact of internal control, financial literacy, and organizational culture on financial performance in LPD Kintamani District. This study uses a quantitative approach. The data collection technique used in this study was in the form of a questionnaire given to the heads of LPDs in the Kintamani District. The data analysis technique used was SEM-PLS (Smart Equation Modeling- Partial Least Square) version 3.0 where the number of samples used in this study were 34 heads of LPD, determining respondents using a purposive sampling technique. The results of the study show that Internal Control has a significant positive effect on Financial Performance in the LPD in Kintamani District. Then Financial Literacy has a significant positive effect on Financial Performance at LPD in Kintamani District. Furthermore,